Governadores e capitães-generais: as ambições políticas dos capitães-mores da Paraíba (primeira metade do século XVIII) (Ágora Journal, 2021)
The captain-majors of Paraíba, throughout the first half of the 18th century, claimed that the captaincy they governed had a superior political status compared to the neighboring captaincies. Based on a political discourse constructed in the local imaginary about the specificity of Paraíba, these captain-majors desired the elevation of the captaincy to a captaincy-general and the granting of the rank of governor and captain-general or marshal field. Furthermore, these authorities also pleaded to increase the governing jurisdiction of their offices. This article, therefore, intends to analyze the strategies and arguments used by these captain-majors to obtain recognition and benefits from the king and the monarchy.